Role of Counselor in Career Interest Aptitude Test for Vocational Students - Wardoyo Wardoyo; Mudjiran Mudjiran; Yeni Karneli (Jurnal Counseling Care, 2024)
The purpose of this research is to find out how counselor play a role in implementing career interest aptitude tests for students of the vocational High School. This research uses a literature review to support the research by looking for relevant theories in journal articles, books, ebooks, and other documents. This research shows that counselor can utilize interest tests to support guidance and counseling at school, especially in placing and disseminating interests according to students' abilities and potential. The results showed that the role of Counselor is very important in helping and directing students to take career interest aptitude tests. Counselor act as facilitators, motivators, and advisors who help students understand themselves, choose careers, and develop their own potential.  The results of this study show how important it is for guidance and counseling teachers to actively participate in preparing students to enter the world of work in accordance with their interests and talents. Consequently, this study suggests that guidance and counseling teachers should be more active and supportive in conducting career interest aptitude tests to improve vocational students' job success and satisfaction.